Women and capital punishment in America, 1840 - 1899: death sentences and executions in the United States and Canada - Segrave, Kerry (McFarland & Co, 2008)
"This book profiles the lives and cases of selected women sentenced to capital punishment in America between 1840 and 1899, most of whom were executed by hanging. The book is divided into chapters by decades, chronologically following the long and heated debate regarding women and capital punishment"--Provided by publisher